2015
DOI: 10.7575/aiac.ijalel.v.4n.4p.46
|View full text |Cite
|
Sign up to set email alerts
|

A large-Scale Study on Extensive Reading Program for Non-English Majors: Factors and Attitudes

Abstract: Reading is a complex method of drawing information from some form of text and then interpreting it. The importance of reading in an academic context cannot be underestimated in its influence on learning. It is commonly agreed that students should read extensively in order to enhance their reading skills and to learn other knowledge through that reading. This paper presents an analysis of teachers' and students' perceptions toward an extensive reading program located in an EFL higher education context. Particul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 19 publications
2
12
0
2
Order By: Relevance
“…The study found that students’ comfort level in L2 reading had been greatly enhanced. Positive feedback was also reported in a large scale study by Tien (2015) with more than 1,000 English as a Foreign Language (EFL) students who had little experience in L2 ER. If reading extensively changes students’ attitudes towards reading, then it is worthwhile to explore what plays the most important role during the reading practice.…”
Section: Literature Reviewmentioning
confidence: 81%
See 1 more Smart Citation
“…The study found that students’ comfort level in L2 reading had been greatly enhanced. Positive feedback was also reported in a large scale study by Tien (2015) with more than 1,000 English as a Foreign Language (EFL) students who had little experience in L2 ER. If reading extensively changes students’ attitudes towards reading, then it is worthwhile to explore what plays the most important role during the reading practice.…”
Section: Literature Reviewmentioning
confidence: 81%
“…Many studies have shown that students’ perceptions of ER change after they have real experience of reading in L2 (Al-Hamound and Schmitt, 2009; de Morgado, 2009; Martinez, 2017; Tien, 2015; Yamashita, 2013). For example, 61 Japanese university students read for 45 minutes in class per week for a 15-week period (Yamashita, 2013).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the study of Tien (2015), attitudes and perceptions on ER were explored in a Taiwanese EFL higher education context. Using descriptive survey method, the study revealed that ER can significantly change attitudes of both teachers and students toward reading.…”
Section: Impacts Of Extensive Reading (Er) On Language Learningmentioning
confidence: 99%
“…Reka bentuk kajian yang dijalankan lebih kepada kaedah campuran kerana gabungan kaedah kualitatif dan kuantitatif dapat memberikan hasil dapatan yang empirikal (Richey & Klein, 2010). Enam kajian gabungan kualitatif dilaksanakan oleh Tien (2015), Sun et al (2016), Iqbal dan Komal (2017), Boakye (2017), Ramonda (2020) dan Rajabpour (2020).…”
Section: Perbincanganunclassified
“…Reka bentuk kajian kualitatif yang dijalankan menggunakan kajian kes iaitu dijalankan olehMikami (2013) di Jepun untuk mengkaji tahap motivasi melalui penetapan matlamat dalam bacaan ekstensif. Satu reka bentuk kajian gabungan kualitatif dan kuantitatif pula menggunakan teori mendasar (Grounded Theory) iaitu kajian yang dijalankan olehSun et al (2016) manakala lima lagi kajian reka bentuk gabungan menggunakan kajian kes (case study) yang dijalankan olehTien (2015),Iqbal dan Komal (2017),Boakye (2017),Ramonda (2020) danRajabpour (2020). Reka bentuk kajian serta instrumen kajian yang digunakan ditunjukkan dalam Jadual 1 dan Jadual 2.Jadual 2: Kaedah dan Instrumen…”
unclassified